PERBANDINGAN KONSEP DASAR PENDIDIKAN ANTARA DEWEY DAN ASY-SYAIBANI - Syabuddin Gade (Jurnal Ilmiah Didaktika, 2011)
This writing tries to compare between the concept of education brought by Dewey, as a modern western educator and asy-Syaibani as an Islamic educator. Both have different background and basic foundation when they formulate the basic concept of education. Therefore, there are some substantial differents and similarity between them. In general, both thoughts can be used to develop the education in Indonesia.